Detection of cytosine deaminase in genetically modified tumor cells by specific antibodies - Haack, Karin; Moebius, Ulrich; Knebel Doeberitz, Magnus von; Herfarth, Christian; Schackert, Hans K.; Gebert, Johannes (Human gene therapy, 1997)
Bacterial cytosine deaminase (CD) converts the non-toxic prodrug 5-fluorocytosine (5-FC) into 5-fluorouracil (5-FU), which is toxic for mammalian cells. Therefore, the CD gene is used in cancer gene therapy to achieve high local concentration of a toxic metabolite without significant systemic toxicity. To allow the detection of CD expression at the protein level, we raised both polyclonal rabbit antisera and a monoclonal antibody (mAb) against a histidine-tagged CD fusion protein. The specificity of the polyclonal antisera and the mAb was confirmed by immunohistochemistry, immunoblot analysis, and immunoprecipitation using CD-expressing tumor cell lines. Furthermore, the antibodies can be used for ELISA assays and flow cytometry. Finally, the CD protein could be demonstrated in frozen tissue sections of CD-modified tumors in a rat tumor model using the anti-CD serum. With these antibodies, CD expression can now be monitored throughout in vitro and in vivo gene transfer studies, including clinical protocols relying on the CD suicide gene strategy.
Elektronische Reproduktion der Druck-Ausgabe 20. März 2008
Gesehen am 21.08.2025